Strength and failure characteristics of brittle jointed rock-like specimens under uniaxial compression: Digital speckle technology and a particle mechanics approach - Cao, Rihong; Lin, Hang; Cao, Ping (International journal of mining science and technology, 2018)
The strength and failure characteristics of most natural rock mass are influenced by discontinues such as fissures, joints, and weak surfaces. In the present study, the strength and failure behavior of ubiquitous-joint rock-like specimens under uniaxial loading have been investigated by DIC (digital image correlation) and discrete element numerical method (PFC2D). The results are obtained. Firstly, the UCSJ of specimens with γ = 15° or 30° shows similar tendency while α goes from 0° to 75°. With γ = 45° or 60°, the UCSJ of specimens increases when α goes from 0° to 30° and decreases after α goes beyond 30°. With γ = 75°, the peak UCSJ value is reached when α = 0°. The UCSJ value shows an increasing trend when α goes from 60° to 75°. Secondly, the ubiquitous-joint specimens present different failure modes for various levels of α and γ(β-α). Based on the experimental results, the failure mode of ubiquitous-joint specimens can be classified into three categories: stepped path failure, failure through parallel plane, and failure through cross plane.